Calculating minimum safety distance against wildfires at the wildland-urban interface in Chile and Spain - Castillo Soto, Miguel (2022)
Wildfires in the urban-forest interface constitute a civil protection emergency, causing considerable personal injury and damage to properties. The potential impacts of wildfires on buildings can be minimized by reducing the surrounding fuel and the use of structural materials with low flammability. However, the costs associated with implementing these actions and the responsibility for maintenance usually present conflicts with the property owners. This study aimed to identify minimum safety distances in wildland-urban interfaces within priority areas. The priority areas were identified based on the integration of fire risk and fuel hazard. Radiant heat is a variable in the behavior of fire that directly influences the definition of safety distances. In this research the radiant heat transfer was calculated based on the potential fire behavior for each study area. A comparative study of the horizontal heat transfer method and the radiant heat flux model was carried out. The horizontal heat transfer method indicated the highest vegetation-free distances, ranging from 23 m to 32 m. Some safety distances were validated using experimental fires and wildfires. The findings from the experimental fires and wildfires emphasize the need for a progressive fuel load reduction to mitigate radiant heat transfer. This may include both the removal of surface fuel and removal of trees to mitigate against crown fires. Our findings provide relevant information for decision-making on the effectiveness and efficiency of safety distances at the wildland-urban interface.